An AHP Approach toward Evaluating IoT Business Ecosystem in Korea - Jaewon Choi; Seongcheol Kim (International Telecommunications Society (ITS), 2018)
The Internet of Things (IoT) has been a major buzz word and is accepted as a future direction of ICT. One of the market's challenges is the formation of healthy business ecosystems. As IoT business inherently encompasses convergence of distinct industries, forming a healthy business ecosystem is challenging. However, there is only limited amount of studies concerning the business ecosystem evaluation. Thus, the current study intends to develop a viable model for assessing the healthiness of IoT business ecosystems. Factors affecting the IoT business ecosystems are suggested in the form of hierarchical decision tree, of which the first layer consists of stability, productivity, and diversity. In the second layer, 7 sub-criteria were presented under each major evaluation factor. Consequently, the health of three Korean IoT business ecosystems were assessed. Using the AHP method, the perceptions of 51 IoT researchers were analyzed. The results showed that the service oriented IoT business ecosystem alternative was the healthiest. Telecom firm's ecosystem showed well distributed capabilities in every factor. Meanwhile, tech-oriented firm's technological strength did not compensate its lack of value creation. Detailed theoretical, practical implications, and limitations of this study are also discussed.
Keywords: 330; Internet of things; IoT; business ecosystem; AHP; multi-criteria decision model; business ecosystem health